Implementation of Maqashid Syari'ah in Resolving Religious Conflicts in Indonesia: A Case Study of the Construction of Houses of Worship and Religious Tolerance - Dhea Kapril Amanda; Rohatul Laeli; Baiq Mila Andriani; Dewi Ratna Hidayati; Humamurrizqi Humamurrizqi (Penerbit Hellow Pustaka, 2026)
This study examines the implementation of maqashid shari’ah in addressing religious conflicts in Indonesia, particularly in issues involving the construction of houses of worship and the practice of interfaith tolerance. Tensions often arise due to differing interests, religious interpretations, and regulatory complexities, making this issue socially significant. The aim of this research is to analyze how maqashid shari’ah especially the protection of religion (hifdz al-din), life (hifdz al-nafs), and intellect (hifdz al-‘aql) can serve as a welfare-oriented framework for conflict resolution and social harmony. The method employed is a literature review by examining legal documents, national regulations, and academic studies related to maqashid shari’ah and religious conflict. The findings indicate that maqashid shari’ah provides a constructive basis for promoting tolerance through interfaith dialogue, fair regulatory implementation, and multicultural education. This research offers both theoretical insights and practical guidance for policymakers, religious leaders, and communities in formulating peaceful and just conflict-resolution strategies.